Shame in the individual lament Psalms and African spirituality - Aidoo, Mark S. (African theological studies, 2017)
Introduction -- Shame in context: encountering the phenomenon of shame in Hebrew Bible, anthropology, and psychology -- Positive petitions for shaming: the rhetoric of shaming the enemy -- Negative petitions for shaming: the rhetoric of the righteous avoiding shame -- The rhetoric of shifting between positive and negative shame -- Creative theological consciousness of the effectiveness of shaming rhetoric -- Shaming toward spirituality - an African cultural perspective -- Conclusion